Performance Analysis the Impact of Solar Panel Placement on the Deck House Fishing Vessel (20 GT) on Fishing Operation - Shanty Manullang; Rizky Irvana; Y. Arya Dewanto; Amelia B.A. Wetik; Mercy Patanda (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
High stability is imperative, safeguarding against the unpredictable nature of the marine environment and promoting a secure working platform for crew members to do fishing operation. The aim of this study is to analyze the effect of laying solar panels on the deckhouse of small fishing vessels 20 GT. The additional load above which causes weight gain and will affect the ship's center of gravity is became the first effect of Fishing vessel stability. The second effect is on how the fishing vessel performs when there is a solar panel on the vessel. The data were collected by measuring the stability according to A.N Kyrylo’s method with standard checks according to the IMO (International Marine Organization). Code on Intact stability calculated the ship motion by using the STRIP method and using the JONSWAP method to measuring the wave characteristics with the help of Maxsurf software. The results of this research show that the installment of solar panels above the deckhouse does not really affect the stability, where the results were meets the IMO standard criteria. The successful fishing operation of the vessels studied will only have a good performance at 1.5 meters, according to the seakeeping analysis.